Evaluasi Pengaruh Multi Segment Periode Produksi Terhadap Akurasi Forecast Decline Curve Analysis pada Sumur 7289 Lapangan Volve - Maulidi Rahmawati; Fatma Fatma; Mirza Mirza (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Daily oil production data often exhibit fluctuations and changing decline trends, which can reduce forecast accuracy when the entire production period is represented by a single decline pattern. This study evaluates the accuracy of a production-period segmentation approach in Decline Curve Analysis for Well 7289 in the Volve Field. The study used 546 daily oil production records classified as USE. Production rates were normalized using On_Stream_Hrs to obtain equivalent 24-hour rates, then divided into Fitting, Validation, and Late Decline segments and modeled using the Arps Exponential equation. Forecast performance was evaluated using RMSE, MAE, MAPE, and R². The model yielded an RMSE of 126.23 STB/day, MAE of 92.31 STB/day, MAPE of 8.57%, and R² of 0.703. The results indicate that segmentation supports a more structured evaluation of production changes. Future studies should apply statistical segmentation criteria and compare alternative decline models.